Development of cut to length machine using programmable logic controller with human machine interface - Mashori, Sumaiya; Ganesen, Ashok Kumar; Lam, Hong Yin; Sahari, Norain; Norjali, Rasida; Sim, Sy Yi (WARSE, 2020)
Industrial automation helps to eliminate the possibility of human error, reducing costs, saves time-consuming, and achieves higher productivity with better quality with the helps of the control system and technologies that enable industrial processes and machinery to operate automatically. For paper cutting applications, an automated cutter that able to cut the paper at specific lengths and operate according to the parameter setting by the user could help to save cost and time. Therefore, this work is to develop a cut to length machine using the Unitronic Jazz Programmable Logic Controller (PLC) with the combination of Human Machine Interface (HMI) features. This work aims to design and fabricate a small scale cutting machine controlled via a PLC software. To enhance the security system, one-stop center control panel is developed. The iron framework is chosen as a basement of the conveyor and cutter, with the fabrication process consists of five stages. The relationship between the measured speeds of the Alternating Current (AC) induction motor over the frequency range is discussed. From the experiment, the result shows that the machine able to cut the paper with a good precision and accuracy at the length of 1, 5, 6 and 7 inch for the paper type of 50, 70 and 80 gram per square meter (gsm) with the constant pneumatic pressure of 7.5MPa and constant motor speed at 60rpm (2Hz).